AETCOM: Navigating the Art of Effective Communication - Nirmala Anand; Rajesh Shenoy; Dhruv Uday Goltekar (Medical Research and Its Applications Vol. 11, 2024)
The Medical Council of India (MCI) has proposed a new teaching method, known as the Attitude, Ethics, and Communication Module (AETCOM), to improve the MBBS syllabus and better address the country’s healthcare requirements. This introduction addresses the shortcomings of the fragmented and neglected traditional methods of teaching empathy and communication, which contributed to a strained doctor-patient relationship and an increase in medicolegal cases. Two years since its introduction, numerous studies have been conducted to evaluate AETCOM’s effectiveness. Yet, lingering questions persist, such as whether incorporating humanities into medicine will blend values and the art of medicine with advancing science. The key inquiry remains: Can it successfully instill integrity in Indian medical graduates, and if not, what measures should be taken for improvement? The authors aim to raise awareness and spark curiosity among both the medical community and the general population through this article, seeking to identify immediate improvements necessary to ensure the development of proficient doctors in the future [1].